Cryogenic phonon-scintillation detectors with NTD germanium readout - Coulter, P (2013)
Cryogenic detectors are an advanced technology for both dark matter and neutrinoless double beta decay searches, having the key advantage of a range of possible absorber materials that can be used for the detectors. Neutron transmutation doped germanium sensors are highly sensitive thermometers ideal for use at milli kelvin temperatures, with a simple repeatable resistance temperature relation. To discriminate between candidate events and background events simultaneous measurements can be made of the energy deposited in the detector as phonons and the energy emitted by the absorber crystal as scintillation light. Phonon detectors with a calcium tungstate or calcium molybdate crystal as the target and an NTD sensor as a thermometer were made in Oxford, along with a light detector with a light-absorbing silicon layer on a sapphire crystal, also with an NTD thermometer. A system of electronics was designed and tested in Oxford to bias and readout the NTD thermometers, while the setup inside the cryostat was developed to provide a thermally and mechanically stable shielded environment for the detectors. As part of this, prototype semi-rigid kapton cabling for use in the EDELWEISS experiment was installed and tested in the cryostat. Three different NTD germanium sensor types were characterized and calibrated in the cryostat and two of these selected for use on the phonon and light detectors. The detectors were operated at temperatures as low as 9 mK and tested with radioactive sources to produce energy spectra. Baseline resolutions of 1.7 keV and 2.5 keV, respectively, were achieved for the calcium molybdate and calcium tungstate phonon detectors. A working scintillation light detector was demonstrated as part of a phonon-scintillation detector module with a suggested application in double-beta decay searches.